The representation of female same-sex homoeroticism in contemporary Indonesian film - Munir, Maimunah (2010)
This paper explores the emergence of non-heterosexual sexuality as a theme in contemporary Indonesian films. Unlike the representation of male and female bonding in Indonesian films of the Soeharto era, which tends to affirm the dominant hetero-patriarchal norms, a number of Indonesian films can be seen as negotiations of new understandings of sexual diversity. Guided by Queer film theory and Tom Boellstorff?s (2005) studies on gay and lesbian communities, the study inquires into how the film Tentang Dia (2005) strives to negotiate ?heteronormativity? and homophobia. Using focus interviews and visual analysis, it looks into the pattern of female non-heterosexual intimacy and friendship and suggests a breaking away from the dominant hetero-patriarchal norms. Finally, the study investigates the strategic devices used by the filmmaker to subvert censorship codes and social taboos in a country where non-heterosexual intimacy and friendship are accommodated, but homosexual identities remain outside the range of socially and culturally sanctioned subjectivities.